1986
DOI: 10.1111/j.1469-8137.1986.tb00599.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF HIGH NUTRIENT ADDITION UPON SEASONAL PATTERNS OF MYCORRHIZAL DEVELOPMENT, HOST GROWTH, AND ROOT PHOSPHORUS AND CARBOHYDRATE CONTENT IN FRAXINUS PENNSYLVANICA MARSH

Abstract: SUMMARYThe effects of Glomus macrocarpum and a high rate of nutrient addition upon growth, root carbohydrate and P content, and mycorrhizal development in green ash {Fraxinus pennsylvanica) seedlings were studied over two growing seasons. Mycorrhizal and simila -ly growing non-mycorrhizal seedlings had similar seasonal patterns in growth and in root carbohydrate and P content. No clear difference in mycorrhizal development as as result of nutrient treatment occurred until the middle of the second growing seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…In the current experiments, however, we achieved beneficial mycorrhizal effects using a substratum with a high level (60%) of inert or low density materials which are not normally conducive to mycorrhiza formation (Ravolanirina 1990, Wood 1991). Our results using relatively high P fertilisation, equivalent to at least 360 kg P ha -1 , are similar to those of Douds and Chaney (1986) and Le Tacon and Bouchard (1988), who also showed mycorrhizal effects with Fraxinus spp. in the presence of high soil P.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In the current experiments, however, we achieved beneficial mycorrhizal effects using a substratum with a high level (60%) of inert or low density materials which are not normally conducive to mycorrhiza formation (Ravolanirina 1990, Wood 1991). Our results using relatively high P fertilisation, equivalent to at least 360 kg P ha -1 , are similar to those of Douds and Chaney (1986) and Le Tacon and Bouchard (1988), who also showed mycorrhizal effects with Fraxinus spp. in the presence of high soil P.…”
Section: Discussionsupporting
confidence: 77%
“…(Clark 1969, Douds and Chaney 1986, Ponder 1984. The latter studies used substrata containing at least one-third soil and no peat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the rate of growth, plant demand for nutrients as well as mineral nutrient allocation, and other benefits attributed to VAM fungi can vary considerably depending on the stage of growth of the plant (Douds and Chaney 1986;Dunne and Fitter 1989). For example, Fitter (1986) and Dunne and Fitter (1989) observed that phosphorus concentrations of plants among various inoculation treatments may vary only during part of the growth cycle.…”
mentioning
confidence: 99%
“…Often, an inverse relationship exists between the level of AMF colonization and the amount of available phosphate in the soil (Douds and Chaney, 1986;. AMF have decreased the biomass of some plant species in high nutrient soils compared to plants without AMF, suggesting that AMF can act as pathogenic parasites Koide, 1985).…”
Section: Environmental Factorsmentioning
confidence: 99%